1994
DOI: 10.1136/gut.35.3.408
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen saturation during endoscopic retrograde cholangiopancreatography: a comparison of two protocols of oxygen administration.

Abstract: Patients having endoscopic retrograde cholangiopancreatography (ERCP) are generally elderly and require sedation while in the prone position. These factors may be expected to aggravate any risk of arterial hypoxia. This study evaluated two protocols of oxygen administration, one with and one without pre-oxygenation. In 25 patients in whom preoxygenation with 4 litres/minute for five minutes before sedation was used, followed by continuous oxygen administration, arterial oxygen saturation did not fail below 90%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 8 publications
1
10
0
Order By: Relevance
“…Several studies have looked at the mode of delivery of supplementary oxygen for patients undergoing upper gastrointestinal endoscopy: oxygen adminstration via nasal catheters [7] or oxygenating mouthguards [8], the effect of different oxygen flow rates [9] on maintenance of normoxaemia, the effect of pre‐oxygenation versus only giving oxygen during endoscopy [10] and the effect of supplemental oxygen during the procedure itself [11]. However, no other study has attempted to compare the effect of varying the time of pre‐oxygenation, as conducted in our study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have looked at the mode of delivery of supplementary oxygen for patients undergoing upper gastrointestinal endoscopy: oxygen adminstration via nasal catheters [7] or oxygenating mouthguards [8], the effect of different oxygen flow rates [9] on maintenance of normoxaemia, the effect of pre‐oxygenation versus only giving oxygen during endoscopy [10] and the effect of supplemental oxygen during the procedure itself [11]. However, no other study has attempted to compare the effect of varying the time of pre‐oxygenation, as conducted in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Rigg et al . [10] and Reed et al . [6] both recommended oxygen supplementation at 4 l.min −1 intranasally, to be given at 5 min and 2 min, respectively, before the start of endoscopy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies have shown a higher rate of hypoxia in ERCPs performed without adequate pre‐oxygenation 49,50 . Hypoxia is more likely to occur within 15 min of commencement of ERCP.…”
Section: Anaesthetic Managementmentioning
confidence: 99%
“…The technique of continuous pre‐oxygenation with 100% oxygen for a few minutes has been found to be superior to the four vital capacity breath technique 52,53 . Rigg et al 50 found pre‐oxygenation with 4 l/min oxygen intranasally for duration of 5 min to be adequate. In their study, pre‐oxygenated patients maintained their saturations above 90%, even with sedation levels likely to cause desaturation.…”
Section: Anaesthetic Managementmentioning
confidence: 99%